Preliminary Stability Estimation And Analysis Of Aeromech I Uav Using Datcom Software - Abdullah , Azizul (2012)

(untitled)
Stability is one aspect of the aircraft performance. Conventional methods such as wind tunnel test, flight test and Computational Fluid Dynamics (CFD) are used for the estimation and analysis of the stability during aircraft design process. Those methods are time consuming and expensive because they cannot determine the stability coefficients directly.Thus, as one of the promising alternative methods, the DATCOM software was employed in the present study, in order to estimate the aerodynamic coefficients and analyze the static and dynamic stabilities at the preliminary design stage of a small Unmanned Aerial Vehicle, UAV AEROMECH I which was developed at the School of Aerospace Engineering, Universiti Sains Malaysia. Unlike the conventional methods, the DATCOM facilitated direct estimation of the static and dynamic stability coefficients. In order to generate the desired stability coefficients of UAV AEROMECH I through the DATCOM, the series of name-list statement listing input variables such as flight condition; the reference area and the length of the wing; the basic configuration synthesis parameters; the basic body geometry parameters; the input data for the aerodynamic surface planforms; the aerodynamic characteristics of the planform surfaces; and the case control card for user specification, were created in the source code. The results obtained from the DATCOM software were verified by comparing with the results from the semi-empirical method and the typical stability values of aircraft. Validation and accuracy of the stability with acceptable percentages of errors were made for all of the stability values. The results showed that the UAV AEROMECH I has the reliable stability in the early design stage. The results also proved that DATCOM has the capability for analyzing the stability of small UAV based on the comparison of results that mention before.